Optimization of Zakat Fundraising Realisation Based on the Measurement of the Zakat Literacy Index in Rural and Urban Communities - Adib Fachri; Citra Etika (Islamic Economics Journal, 2024)
This article compares zakat literacy between rural and urban communities in Lampung Province and explores strategies to optimize zakat fundraising based on the Zakat Literacy Index (ILZ) of each region. Using a mixed method approach with an explanatory design, 200 respondents were involved, with 100 from rural and 100 from urban areas. The independent t-test results show a difference in zakat literacy between the two groups, although the difference is not statistically significant. The ILZ in rural areas is 79.57 (medium category), while in urban areas it is 86.79 (high category), reflecting a relatively good understanding in both communities. To optimize zakat fundraising, urban areas can focus on strengthening technical management and adopting digital technology for payments, while rural areas require educational efforts and collaboration with religious leaders to enhance basic zakat knowledge.